The Study of Swedish Massage on Anxiety Situation and PPT in Stressed Office Workers.. (Medico Legal Update, 2020)
Background: The purpose of this study was to investigate the effects of Swedish massage on anxiety and pressure pain threshold in office workers with psychological stress.Method: Sixty office workers with psychological stress were randomly assigned to experimental group 1 and control group. They were assigned into either a Swedish massage group (Experimental group 1, n = 30) or a resting group (Control group, n = 30). A single measurement mediated Swedish massage and rest for 20 minutes and was measured before and after intervention.Findings: In state trait anxiety inventory (STAI), there were significant differences between before and after the experiment and between the two groups (p